Noradrenergic changes, aggressive behavior, and cognition in patients with dementia. - Matthews, K; Chen, C; Esiri, M; Keene, J; Minger, S; Francis, P (2002)
BACKGROUND: We wished to examine the integrity of the noradrenergic system in patients with Alzheimer's disease, mixed/other dementias and controls, and possible relationships between changes in the noradrenergic system and the presence of behavioral and psychiatric signs and symptoms in dementia. METHODS: Alpha(2) adrenoceptor sites were measured by radioligand binding in three cortical regions of 46 individuals with dementia and 33 elderly normal controls together with cortical noradrenaline concentration and locus coeruleus cell and neurofibrillary tangle counts. RESULTS: The alpha(2) adrenergic receptor density was unaltered in patients with Alzheimer's disease, mixed/other dementias compared with controls; however, there was a loss of locus coeruleus cells in subjects with dementia, reaching 50% within the rostral nucleus. In addition, a significant reduction was seen in the midtemporal cortical noradrenaline concentration (31% decrease) in patients with Alzheimer's disease. In subjects with dementia, there was a positive correlation between aggressive behavior and magnitude of rostral locus coeruleus cell loss, while the reduction in noradrenaline concentration correlated with cognitive impairment. CONCLUSIONS: Subgroups of patients with Alzheimer's disease may have different neurochemical changes from patients lacking these changes. Therefore, this study may have implications for the treatment of behavioral and psychiatric signs and symptoms in dementia, particularly aggressive behavior in patients with dementia.